Dynamic characteristics of two cylinders' joint surfaces based on fractal theory. (2016) - Xiaopeng, Li; Xue, Wang; Jiasheng, Li; Muyan, Li; Shujun, Li
In order to study the influence of joint surface on the functional performance of mechanical system such as robotics, NC machine tool etc, the elastic-plastic deformation and the friction are considered in the modified M-B fractal model, which has geometric characteristics and scale independence. Then the fractal model of contact stiffness between two cylinders' joint surfaces is established. By comparing the traditional model and the new model in this paper, the influences of elastic-plastic deformation and friction are clearly shown with numerical simulation. Moreover, the cylindrical joint surface is taken as a research object. With the spring element, dynamic model of the cylindrical joint surface is established. Finally, the natural frequency of theory and experiment is compared. The results show the established stiffness model is consistent with the reality and more accurate than the traditional model. Then a reference for solving surface contact problems is completely provided.